If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -1p = 1 Solving 8 + -1p = 1 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1p = 1 + -8 Combine like terms: 8 + -8 = 0 0 + -1p = 1 + -8 -1p = 1 + -8 Combine like terms: 1 + -8 = -7 -1p = -7 Divide each side by '-1'. p = 7 Simplifying p = 7
| n^3-3n^2+2n-60=0 | | (x+5)*(x+5)*(x+5)=1280 | | 18x+15-15x+26=-4+7+9x+6 | | 12-3(-4-2y)=-5 | | 18x+15+15x+26=-4+7+9x+6 | | 6-5=2 | | 5+8i=0 | | y=tan(6x) | | 12+13=x | | -7-13z+15+16z=57-5z+4z-52 | | (2x-1)(3x-2)=33 | | 3x+14+6x-29=43+8x-70-32 | | 3x+14+6x-29=m-3+4m-4 | | 12m+6n-6m+10n= | | 10m+12-4m-19=m-3+4m-4 | | (3x+y^2+2y^5)dx+(2x^2y+5xy^4)dy=0 | | x^2-12i=5 | | 7+9d-4-4d=5d+3-d+8 | | 10x-5+2=7x+21 | | -2(2x+3)-4=-7 | | 5j*6y= | | 3x+y-15=0 | | 4y+5y=6 | | -8t+16=7(10-8t) | | 10+3x-2+x=3x+6+2x+8 | | -15-2(-3y+5)=10 | | 5x+8-3x-11=3x-5 | | 4(3t-2)=5(2t+3) | | 10h-29=51 | | 2(-3y+5)+15=10 | | 25-30+9x=6x-20 | | 1/3(4x-44)=5x |